Assessing bottom trawling impacts based on the longevity of benthic invertebrates. Issue 5 (10th November 2018) - Hiddink, Jan Geert; Jennings, Simon; Sciberras, Marija; Bolam, Stefan G.; Cambiè, Giulia; McConnaughey, Robert A.; Mazor, Tessa; Hilborn, Ray; Collie, Jeremy S.; Pitcher, C. Roland; Parma, Ana M.; Suuronen, Petri; et al.
Abstract: Bottom trawling is the most widespread human activity directly affecting seabed habitats. Assessment and effective management of the effects of bottom trawling at the scale of fisheries requires an understanding of differences in sensitivity of biota to trawling. Responses to disturbance are expected to depend on the intrinsic rate of increase in populations ( r ), which is expected to be linearly related to the reciprocal of longevity. We examine the relationship between the longevity of benthic invertebrates and their response to bottom trawling; both in terms of the immediate mortality following a trawl pass and their subsequent rates of recovery. We collate all available data from experimental and comparative trawling studies, and test how longevity influences these aspects of sensitivity. The shortest lived organisms (<1 year) increased in abundance shortly after experimental trawling but showed no response to trawling in long‐term comparative studies. Conversely, the abundance of biota with a life span >1 year decreased by 9% immediately following a trawl pass. The effect of bottom trawling in comparative studies increased with longevity, with a 2–3× larger effect on biota living >10 years than on biota living 1–3 years. We attribute this difference to the slower recovery rates of the long‐lived biota. The observed relationship between the intrinsic rate of population increase ( r, our metric of recovery rate) and the reciprocal of longevity matches theoretical expectation and predicts that the sensitivity of habitats to bottom trawling is higher in habitats with higher proportions of long‐lived organisms. Synthesis and applications . Where the longevity of a species or the longevity distribution of a community is known or can be inferred, our estimates of depletion and intrinsic rate of increase can be combined with high‐resolution maps of trawling intensity to assess trawling impacts at the scale of the fishery or other defined unit of assessment. Our estimates of r may also be used to estimate recovery times following other forms of seabed disturbance. Abstract : Where the longevity of a species or the longevity distribution of a community is known or can be inferred, our estimates of depletion and intrinsic rate of increase can be combined with high‐resolution maps of trawling intensity to assess trawling impacts at the scale of the fishery or other defined unit of assessment. Our estimates of r may also be used to estimate recovery times following other forms of seabed disturbance. Foreign Language Abstract Overzicht Beoordelen van bodemvisserijeffecten op basis van de levensduur van bentische ongewervelde dieren: Trawlvisserij op de zeebodem is de meest voorkomende menselijke activiteit met rechtstreekse gevolgen voor habitats op die zeebodem. Om de effecten van bodemtrawls op de schaal van de visserij te kunnen beoordelen en effectief te beheren, is inzicht nodig in gevoeligheid voor trawlvisserij van verschillende dieren. Reacties op verstoringen zullen naar verwachting afhangen van de intrinsieke groeisnelheid van populaties ( r ). We verwachten dat die omgekeerd evenredig is aan de levensduur van soorten. We onderzoeken de relatie tussen de levensduur van bentische ongewervelde dieren en hun reactie op bodemtrawls; zowel in termen van de onmiddellijke sterfte na een trawltrek als van de daaropvolgende herstelpercentages. We verzamelen alle beschikbare gegevens uit experimentele en vergelijkende trawlonderzoeken en testen hoe de levensduur van soorten deze aspecten van gevoeligheid beïnvloedt. De aantallen kortlevende organismen (<1 jaar) namen toe kort na experimentele trawlvisserij, maar vertoonden in vergelijkende studies op langere termijn geen reactie op trawlvisserij. De talrijkheid van dieren met een levensduur >1 jaar nam af met 9% onmiddellijk na een trawltrek. Het effect van bodemtrawls in vergelijkende studies nam op langere termijn toe met de levensduur. Er was een 2–3× groter effect op dieren die >10 jaar leefden dan op dieren die 1–3 jaar oud worden. We schrijven dit verschil toe aan het tragere herstel van de langer levende dieren. De waargenomen relatie tussen de intrinsieke snelheid van de toename (r) en het omgekeerde van de levensduur van een soort komt overeen met de theoretische verwachting. Hiermee wordt voorspeld dat de gevoeligheid van habitats voor bodemtrawls hoger is als er sprake is van hogere percentages langlevende organismen. Synthese en toepassingen . Als de levensduur van een soort of de levensduur van een gemeenschap bekend is of kan worden afgeleid, kunnen onze schattingen van sterfte en intrinsieke groeisnelheid worden gecombineerd met hoge resolutie kaarten van de intensiteit van de trawlvisserij om de impact van trawlvisserij op de schaal van de visserij te bepalen.